PERUBAHAN LINGKUNGAN, TRANSFORMASI ORGANISASIONAL DAN REPOSISI PERAN FUNGSI SUMBERDAYA MANUSIA - Gugup Kismono (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
The environment within which an organization operates is dynamic and has become much more diverse and complex. The environment has a profound impact on the organization's success. In today's changing, the firm faces many challenges not faced before. The company's ability to adopt or amend strategies to compensate for or take advantage of such changes will dictate its success and even survival. A change in strategy will determine its organization structure and the direction of each function within the organization, including the human resource management function. Human resource management function has expanded and moved beyond mere administration of the traditional activities. Today human resource management function is much more integrated into both the management and the strategic planning process of the organization. In order to be effective, the human resource management function must continually cultivate good relations with operating functions. Also, the company's human resource professional must acquire business knowledge competence so she/he able to understand the operating functions. Likewise, operating functions (and also the excecutives) must understand the new role of the human resource functions to effectively utilise the human resource services. This article reviews the impact of the external and internal forces to human resource management function. The forces are changing the rules of the game. The human resource management function becomes much more integrated into management and the strategic planning process. It also has a new role. In order to be effectively functional, the human resource professional must acquire new skills and builds new relationships with the operating functions. Manajemen Sumberdaya Manusia (MSDM) tengah menghadapi tantangan baru seiring dengan perubahan lingkungan eksternal dan lingkungan internal yang semakin dinamis. Tantangantantangan iersebut berkaitan dengan globalisasi, karyawan yang semakin beranekaragam, perubahan peraturan, perubahan struktural organisasi, serta perubahan teknologi (Byars dan Rue, 1997).